Glutathione Protects Lactococcus lactis against Oxidative Stress - Li, Yin (American Society for Microbiology, 2003)
Glutathione was found in several dairy Lactococcus lactis strains grown in M17 medium. None of these strains was able to synthesize glutathione. In chemically defined medium, L. lactis subsp. cremoris strain SK11 was able to accumulate up to ∼60 mM glutathione when this compound was added to the medium. Stationary-phase cells of strain SK11 grown in chemically defined medium supplemented with glutathione showed significantly increased resistance (up to fivefold increased resistance) to treatment with H(2)O(2) compared to the resistance of cells without intracellular glutathione. The resistance to H(2)O(2) treatment was found to be dependent on the accumulation of glutathione in 16 strains of L. lactis tested. We propose that by taking up glutathione, L. lactis might activate a glutathione-glutathione peroxidase-glutathione reductase system in stationary-phase cells, which catalyzes the reduction of H(2)O(2). Glutathione reductase, which reduces oxidized glutathione, was detectable in most strains of L. lactis, but the activities of different strains were very variable. In general, the glutathione reductase activities of L. lactis subsp. lactis are higher than those of L. lactis subsp. cremoris, and the activities were much higher when strains were grown aerobically. In addition, glutathione peroxidase is detectable in strain SK11, and the level was fivefold greater when the organism was grown aerobically than when the organism was grown anaerobically. Therefore, the presence of glutathione in L. lactis could result in greater stability under storage conditions and quicker growth upon inoculation, two important attributes of successful starter cultures.